2015
DOI: 10.1080/08957959.2015.1005013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high hydrostatic pressure on secondary structure and emulsifying behavior of sweet potato protein

Abstract: 2015): Effects of high hydrostatic pressure on secondary structure and emulsifying behavior of sweet potato protein, HighIn this study, secondary structures of sweet potato protein (SPP) after high hydrostatic pressure (HHP) treatment (200-600 MPa) were evaluated and emulsifying properties of emulsions with HHP-treated SPP solutions in different pH values (3, 6, and 9) were investigated. Circular dichroism analysis confirmed the modification of the SPP secondary structure. Surface hydrophobicity increased at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…EAI and ES index (ESI) were reported to be increased by HPP treatments (200 to 600 MPa) for potato protein at pH 6 to 9 (Khan, Mu, Sun, Zhang, & Chen, 2015). The EAI of red kidney bean protein isolate, similar to its ESI increased significantly from 24.2 to 40.4 m 2 /g with increasing pressure from 0.101 to 400 MPa and then decreased to 33.9 m 2 /g with further increase in pressure to 600 MPa whereas its FC and FS decreased with pressure levels (200 to 600 MPa; Ahmed, Al‐Ruwaih, Mulla, & Rahman, 2018).…”
Section: Modification Of Plant Proteins By Various Processing Techniquesmentioning
confidence: 99%
“…EAI and ES index (ESI) were reported to be increased by HPP treatments (200 to 600 MPa) for potato protein at pH 6 to 9 (Khan, Mu, Sun, Zhang, & Chen, 2015). The EAI of red kidney bean protein isolate, similar to its ESI increased significantly from 24.2 to 40.4 m 2 /g with increasing pressure from 0.101 to 400 MPa and then decreased to 33.9 m 2 /g with further increase in pressure to 600 MPa whereas its FC and FS decreased with pressure levels (200 to 600 MPa; Ahmed, Al‐Ruwaih, Mulla, & Rahman, 2018).…”
Section: Modification Of Plant Proteins By Various Processing Techniquesmentioning
confidence: 99%
“…This behavior is typical of associative weak interactions [19] and has been reported for different protein-based emulsions. [20][21][22][23][24][25] This physical behavior can be attributed to different microscopic factors, such as changes in spatial distribution of disperse particles due to shear forces, alignment of non-spherical droplets, removal of solvent molecules bonded to droplets, and deformation and rupture of flakes. [26] The Herschel-Bulkley model was well fitted to the data (Table 2), leading to R 2 > 97% and AMPE < 11% for all studied conditions.…”
Section: Influence Of the Number Of Homogenization Passesmentioning
confidence: 99%
“…Therefore, the surface hydrophobicity was reduced [ 45 ]. Khan et al [ 46 ] and Li et al [ 24 ] also found that the interaction between proteins and polysaccharides caused changes in protein secondary structure and aggregation, and that hydrophobic amino acids were less exposed to the protein surface in the presence of polysaccharides. However, the mechanical force in the process of stirring and homogenization destroys and disperses the aggregated and denatured proteins, causing the hydrophobic groups to be fully exposed, allowing proteins to quickly undergo the stages of diffusion, adsorption, structural rearrangement, crosslinking, and solidification to form an interfacial film of bubbles or emulsion droplets [ 47 ].…”
Section: Resultsmentioning
confidence: 99%